Communication in songs inspired by the news: memory construction of victims - Figueroa-Bustos, Arturo (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
For centuries, the news has inspired musicians' creativity. Based on the journalistic functions of music, this article analyzes the recursive ways in which news can inspire a group of creative musicians and how, in turn, these songs become vehicles for communicating those news pieces. In order to do so, it conducts a qualitative analysis of interviews with Chilean composers who explain, in a podcast, the creation of 10 news-inspired songs. The findings show that, fundamentally, Chilean news-inspired songs refer to anonymous people who experience tragic, life-threatening events, which, for the composers, are significant stories in terms of values ​​that should not be forgotten.
Keywords: news; songs; music and inspiration; textual analysis; podcast